Cracking the stress problem - Willis, Richard J. B. (Grantham : Stanborough Press, 2005)
The book addresses the issues of understanding what stress is and how to cope with it effectively.
.Includes bibliographical references.
oif 27/12/13
Loan
Keywords: Stress management; Stress (Psychology)